BIOLOGICAL TREATMENT OF WASTE WATER OF FOOD INDUSTRY ENTERPRISES (IN THE CASE OF KOKAN BREAD FACTORY) (British Journal of Global Ecology and Sustainable Development, 2024)
In this article, we explore the world of industrial wastewater biological treatment and explore innovative strategies and emerging technologies to improve its efficiency. By addressing these challenges and implementing advanced solutions, the industry will not only meet stringent regulatory requirements, but also ensure a cleaner and more sustainable future for us. The treatment of wastewater from a bread production plant with the help of pistachio plant (Pistia Stratiotes L) was studied and the efficiency of biological treatment of wastewater was studied. The pistachio plant is used as an additional feed and fattening is observed in animals such as sheep and cows that are raised for consumption. The pistachio plant has been proven to be natural and harmless. Biological treatment is one of the most economically acceptable methods of wastewater treatment, and this method is proven in the article based on laboratory results, the cultivation of aquatic plants, and the use of them. The daily average growth of pistachio biomass in the wastewater of Dangara bread production industry is 900-1300 g/m2, in the diet of agricultural animals and poultry after thermal treatment of the biomass of high water plants grown in wastewater it is recommended to use it as a bio-additive.